2022
DOI: 10.3390/brainsci12050551
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Romantic Love: A Review of EEG and ERP Studies with Beloved-Related Stimuli

Abstract: Science is starting to unravel the neural basis of romantic love. The goal of this literature review was to identify and interpret the electrophysiological correlates of romantic love. Electroencephalography (EEG) and event-related potential (ERP) studies with a design that elicits romantic love feelings were included. The methods of previous EEG studies are too heterogeneous to draw conclusions. Multiple ERP studies, however, have shown that beloved stimuli elicit an enhanced late positive potential (LPP/P3/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…However, alpha frequency bands are high during relaxation and beta and gamma frequency bands are high during cognitive processing. 27 In a study on the effect of love emotion on face perception, the EEG recordings were taken by showing pictures of the loved person, appreciated friend, unfamiliar person and a blank page to people in a romantic love relationship (20 women). As a significant finding of the study, they observed that higher delta amplitude values (0.5-3 Hz) occurred on the frontal electrodes when the picture of the person they fell in love with was shown.…”
Section: G) Cerebral Cortexmentioning
confidence: 99%
“…However, alpha frequency bands are high during relaxation and beta and gamma frequency bands are high during cognitive processing. 27 In a study on the effect of love emotion on face perception, the EEG recordings were taken by showing pictures of the loved person, appreciated friend, unfamiliar person and a blank page to people in a romantic love relationship (20 women). As a significant finding of the study, they observed that higher delta amplitude values (0.5-3 Hz) occurred on the frontal electrodes when the picture of the person they fell in love with was shown.…”
Section: G) Cerebral Cortexmentioning
confidence: 99%
“…The study of love encompasses different perspectives from diverse disciplines, such as anthropology, genetics, biology, neurobiology, and psychology ( De Boer et al, 2012 ; Carter and Porges, 2013 ; Cacioppo and Cacioppo, 2015 ; Tobore, 2020 ; Langeslag, 2022 ). There is general agreement in describing love as a complex emotion, having multiple expressions ( Hatfield and Sprecher, 1986 ) and favoring long-term mating ( Sorokowski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%